MEASURING THE GOVERNANCE CAPABILITY OF THE BYOND BY BSI APPLICATION USING COBIT 2019: FOCUSING ON THE DSS02 DOMAIN FOR STRENGTHENING MANAGEMENT INFORMATION SYSTEMS - Rosid, Achmat; Lailiya, Nurul; Shina, Muchammad Yusril Ibnu (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Digital technology has rapidly developed over time, particularly in the banking sector. A concrete example of this development is the emergence of mobile banking (m-banking) services. BYOND by BSI is a new m-banking application owned by Bank Syariah Indonesia, whose number of users continues to grow. Therefore, Bank BSI needs to improve the quality of its services to meet customer needs and expectations. In addition, within the context of digital business, the presence of Management Information Systems (MIS) plays a crucial role as it integrates data, facilitates decision-making processes, and supports technology-based service strategies to become more effective and efficient. This study aims to measure the capability level of the BYOND by BSI application using the COBIT 2019 framework, focusing on the DSS02 domain (Manage service requests and incidents). Data collection was carried out through questionnaires distributed to 100 respondents. The results show that the average capability level of the DSS02 domain is 3.64, which is at level 4 (Quantitative Process). Nevertheless, improvements are still needed, particularly in problem resolution and data security protection, so that the application services can be further optimized to support Bank Syariah Indonesia’s digital business.. Keywords: management information systems, capability, byond by bsi, cobit 2019